BALANCE IMPROVEMENT IN OLDER ADULTS WITH TAEKWONDO - Bình Minh, Trần (Journal of Health and Aging, 2026)
Impaired balance in older adults can directly lead to falls, leading to injuries, reduced quality of life, and increased dependence in daily activities. To diversify neuromotor exercises, evidence on the effectiveness of Taekwondo has been reviewed. Searches using relevant keywords reported that Taekwondo significantly improves both static and dynamic balance measures in individuals over 65 years old. Additionally, the findings suggest that Taekwondo may enhance exercise adherence among participants. These results support the potential of Taekwondo as a exercise to improve balance for older adults, although further high-quality evidence is needed.